Bioética no exercício profissional do serviço social: uma análise sob a ótica da ontologia social de Marx - Melo, Luciana Maria Cavalcante (2009)
The present work had as aim to configure the panorama of the Bioethics while as an urgent and necessary subject of professional confrontation in the scope of the Social Service. So for this interlocution became possible, it was necessary to lean over two areas the first one is eminently philosophical, and the second area is strongly calcada in the praxis -, witch was made under the optics of the Ontology of the Social Being of Marx, who emphasizes the work as central category of the social relations and, in accordance with Lukács, that allows the conciliation of the theoretical postulations with the practical necessity. Bioethics is a discipline currently consolidated in the area of sciences and health, is the field of the ethics that considers to study and to intervene in the quandaries and decurrent ethical-politician-social conflicts of the positioning of the society in relation to human being and animals life. Already the Social Service perform in the spoliation reality, of vulnerability and social inequality provoked by the system of politician-economic system so, therefore, it consists in a historical expression of the social matter. The more persistent bioethics conflicts and quandaries in the practical professional of the Social Service had been purpose of qualitative research, configured in interviews with social assistants of a basic unit of health (2), a public hospital (2) and a feminine prison (2). The analysis of the gathered information, also realized through to the light of qualitative method, witch demonstrated that this method does not precede the reality, in contrast: the reality is what determines the adjusted method of analysis for its apprehension. Moreover, the undertaken research is configured as starting point in the inquiry of the interface study between Bioethical and Social Service, as they demonstrate the transcribed testimony. The accesses to the service, and in more analytical way, the access to the social rights, were one of the subjects more brought up in the dialogues. It s already present in the interior of the professional work the bioethics, but that currently demands an effort of theoretical-philosophical register that can contribute with the reflections of these professionals in there daily work